2009
DOI: 10.1017/s0033291709005972
|View full text |Cite
|
Sign up to set email alerts
|

The functional neuroanatomy of blood-injection-injury phobia: a comparison with spider phobics and healthy controls

Abstract: These results suggest partially distinct neurobiological substrates of animal and BII phobias and support their current classification as two distinct subtypes in the DSM-IV-TR. Further research is needed to better understand the precise neurobiological mechanisms in BII phobia and particularly the fainting response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
54
4
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 23 publications
10
54
4
2
Order By: Relevance
“…Identical contrast estimates clearly deviating from zero in all three groups argue against this hypothesis. Lack of activation within the fear circuitry in BII is further supported by previous studies (Caseras et al, 2010a;Hermann et al, 2007;Schienle et al, 2003). It should be noted, however, that those and present findings may be limited to sustained emotional responses in BII phobia, since different results have been obtained for rapid and transient fear reactions (Caseras et al, 2010b).…”
Section: Contrast/regionsupporting
confidence: 88%
See 2 more Smart Citations
“…Identical contrast estimates clearly deviating from zero in all three groups argue against this hypothesis. Lack of activation within the fear circuitry in BII is further supported by previous studies (Caseras et al, 2010a;Hermann et al, 2007;Schienle et al, 2003). It should be noted, however, that those and present findings may be limited to sustained emotional responses in BII phobia, since different results have been obtained for rapid and transient fear reactions (Caseras et al, 2010b).…”
Section: Contrast/regionsupporting
confidence: 88%
“…Based on previous findings (Caseras et al, 2010a;Hermann et al, 2007) we did not assume to detect typical fear circuit activation patterns in dental phobics; instead, modulation of phobogenic responses by orbitofrontal areas was expected. In a first step, we investigated the specificity of neural activations in phobics, comparing them to both a healthy and an analogue phobic control group.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…[20] Conversely, individuals with B-I-I phobia responded to their phobic stimulus with significantly increased activation in the bilateral occipito-parietal cortex and thalamus compared to individuals with spider phobias. [20] While this research suggests neural differences between B-I-I phobia and animal phobia, there is very limited research examining neural differences between other SP types.…”
Section: Resultsmentioning
confidence: 98%
“…Unfortunately, results are rather inconclusive and seem to critically depend on experimental designs and procedures. Confrontation with phobia-relevant or generally disgusting images has been associated with diminished medial prefrontal cortex (PFC) activity (Hermann et al, 2007) and relatively unspecific activations in thalamus and occipital cortex in BII phobics (Caseras et al, 2010a, Schienle et al, 2003). Direct comparison between BII and animal phobics revealed that only spider phobics showed activations in key areas for emotional processing, i.e.…”
Section: Introductionmentioning
confidence: 99%